Response Surface Methodology (RSM) A Good Optimizer for Transesterification Reaction of Chrysophyllum Albidium Seed Oil to Chrysophyllum Albidium Oil Biodiesel (International Journal of Chemical and Process Engineering Research, 2014)
In an effort to optimize the reaction conditions of biodiesel production from Chrysophyllum albidium seed oil, Response Surface Methodology (RSM) was applied and the effects of reaction temperature (X1), catalyst amount (X2), reaction time (X3) and methanol/oil molar ratio (X4), and their reciprocal interactions were examined. A total of 30 experimental runs were generated based on Central Composite Design (CCD) and carried out. A quadratic polynomial was obtained for predicting the transesterification process and the ANOVA test showed the model to be significant (p